The Administration of Morocco during the Era of the Aleamiriuwn Hijabs in Andalusia 367-399 AH/978-1009 AD - Al otaibi , Fawzi Inad alqaburiu (Jordan Journal for History and Archaeology, 2024)
In the last third of the fourth century AH / tenth century AD, the administrators of al-Mansur ibn Abi ‘Amir officially took control of the reins of power in Andalusia (367-399 AH - 978-1009 AD), and Morocco was of strategic importance to them. Therefore, Morocco was of great importance in their policies, and this in turn cast a shadow on various aspects politically, economically, militarily, and socially on Morocco and Andalusia alike. The stage of control of the administrators of al-Mansur ibn Abi ‘Amir over Andalusia constitutes a dangerous turning point in the history of Andalusia and Morocco alike, especially in their management of Moroccan affairs and its repercussions on them, which was evident after their fall, and was confirmed by the events after that with the great change in the political and social map in Andalusia and Morocco at that time. Accordingly, in this research, we will try to trace the way the administrators of al-Mansur ibn Abi ‘Amir managed Morocco and their policies there, monitor and analyze them, and then their consequences and we conclude the research with a summary of the most prominent findings.